Lymphodepletion chemotherapy followed by donor leukocytes for post‐transplantation relapse of myelofibrosis after previous donor leukocyte infusion failure. (29th November 2012) - Neave, Emma Lucy; Schwarb, Heike; Shlebak, Abdurrazag; Layton, David Mark; Apperley, Jane F.; Pavlu, Jiri
Abstract Treatment of relapse after allogenic stem cell transplantation (allo‐SCT) is challenging. The efficacy of donor leukocyte infusions (DLI) is excellent in chronic phase chronic myeloid leukaemia but limited in other disorders. We present a patient who relapsed 10 months after reduced intensity conditioning allo‐SCT for a myelodysplastic/ myeloproliferative neoplasm with myelofibrosis despite receiving escalating doses of DLI for incomplete chimerism. He finally achieved complete remission with full whole blood and T‐cell donor chimerism after DLI preceded by lymphodepletion chemotherapy. This case demonstrates that chemotherapy prior to DLI is a useful approach for treating relapses of relatively slowly progressive diseases, such as myeloproliferative diseases or myelodysplastic syndromes.